Resources, rights, and cooperation: a sourcebook on property rights and collective action for sustainable development - CGIAR Systemwide Program on Collective Action and Property Rights (International Food Policy Research Institute, 2011)
This sourcebook was developed from original research outputs identified by the CAPRi team, mainly from the research work it supported via its global network, supplemented by key pieces from other experts. Most of the readings are from social science researchers working in the fields of agriculture, natural resource management, and poverty reduction, often as part of multidisciplinary teams. In addition, many of the pieces are based on “research for development” that involved not only scientists, but also development practitioners and communities.